The Effect of Additive Manufacturing Adoption, Process Optimization Tools, and Energy Management Systems on Sustainability Performance in Indonesian Industrial Plants - Dharmayanti, Indrani; Rakhmasari, Aster Aryati (Eastasouth Institute, 2025)
This study investigates the effect of Additive Manufacturing (AM), Process Optimization Tools (POT), and Energy Management Systems (EMS) on Sustainability Performance (SP) in Indonesian industrial plants. A total of 85 industrial plants were surveyed, and data was analyzed using Structural Equation Modeling - Partial Least Squares (SEM-PLS 3). The results reveal that AM has the most significant impact on sustainability performance, with process optimization tools and energy management systems also contributing positively. Specifically, AM was found to have the strongest influence on resource efficiency and waste reduction, while POT and EMS helped optimize production processes and energy use, respectively. These findings suggest that the combined adoption of these technologies can substantially improve sustainability outcomes in Indonesian industrial plants. The study highlights the importance of embracing advanced manufacturing technologies, process optimization, and energy management strategies to achieve sustainable industrial development in Indonesia.